The Clinical and Genomic Epidemiology of Rhinovirus in Homeless Shelters—King County, Washington . (24th June 2022) - Chow, Eric J; Casto, Amanda M; Roychoudhury, Pavitra; Han, Peter D; Xie, Hong; Pfau, Brian; Nguyen, Tien V; Sereewit, Jaydee; Rogers, Julia H; Cox, Sarah N; Wolf, Caitlin R; Rolfes, Melissa A; et al.
Abstract: Background: Rhinovirus (RV) is a common cause of respiratory illness in all people, including those experiencing homelessness. RV epidemiology in homeless shelters is unknown. Methods: We analyzed data from a cross-sectional homeless shelter study in King County, Washington, October 2019–May 2021. Shelter residents or guardians aged ≥3 months reporting acute respiratory illness completed questionnaires and submitted nasal swabs. After 1 April 2020, enrollment expanded to residents and staff regardless of symptoms. Samples were tested by multiplex RT-PCR for respiratory viruses. A subset of RV-positive samples was sequenced. Results: There were 1066 RV-positive samples with RV present every month of the study period. RV was the most common virus before and during the coronavirus disease 2019 (COVID-19) pandemic (43% and 77% of virus-positive samples, respectively). Participants from family shelters had the highest prevalence of RV. Among 131 sequenced samples, 33 RV serotypes were identified with each serotype detected for ≤4 months. Conclusions: RV infections persisted through community mitigation measures and were most prevalent in shelters housing families. Sequencing showed a diversity of circulating RV serotypes, each detected over short periods of time. Community-based surveillance in congregate settings is important to characterize respiratory viral infections during and after the COVID-19 pandemic. Clinical Trials Registration: NCT04141917.